Defining quality bulk tonnage: A task for researchers and policy-makers - Helen A. Thanopoulou; Bernard M. Gardner (SPOUDAI - Journal of Economics and Business, 2012)
The aim of this paper is to propose a set of suitable variables on which a comprehensive definition of quality bulk shipping can be built. The authors of this paper explore the alternatives of quality differentiation in bulk shipping, in view of the methodological and data problems researchers have encountered by the absence of a definition of quality for traditional bulk tonnage that goes beyond catch-all indicators such as the age of the vessel. The lack of appropriate available data for the otherwise extensively, yet not necessarily systematically documented, bulk shipping markets, calls for concerted action on the part of researchers and policy makers to compile such databases and make them publicly (widely) available.
Keywords: R41; N70; L91; 330; Quality Shipping; Bulk Shipping; Shipping policy